The Singular Temperley-Lieb Category. (24th April 2014) - Caprau, Carmen; Smith, Joel
Abstract : We introduce and study the singular Temperley-Lieb category overℤ [ q, q - 1 ], which is a free pivotal category over two self-dual generators and is an extension of the (classical) Temperley-Lieb category. Our construction is motivated by a state model for thes l ( 2 ) polynomial of an oriented link and provides a categorical perspective to this link invariant. We also construct a couple of polynomial invariants for oriented tangles from category theory point of view.